Integrating Spirituality in Teaching English to Young Learners based on the Independent Curriculum in Elementary Schools - Taranindya Zulhi Amalia; Januarius Mujianto; Sri Wuli Fitriati; Utami Widiati (International Conference on Science, Education, and Technology, 2022)
Abstrak. Teaching English to Young Learners started in 1994 at the elementary school level. 2022 will be the first year for English as an elective subject in the Merdeka Curriculum. As the name implies, there is no obligation for schools to use this curriculum. As an example, the Integrated Islamic Elementary School is one of the levels that are acquainted with this curriculum only in grades one and four. Although it has a mission to integrate the curriculum of the Ministry of National Education and the curriculum of the Integrated Islamic School, in reality not all English teachers in Islamic schools easily integrate their spiritual values. It aims to integrate spirituality in teaching English to young learners at the elementary school level by applying Independent Curriculum-based and specialist. This research and development are a bridge in answering the teacher's needs for this. The results of this research are teachers need a reference for integrating spirituality in teaching English as a subject in an Integrated Islamic school that combines the Independent Curriculum with the Integrated Islamic Elementary School Curriculum. In language skills development, reading and writing become the focus of the average teacher. Meanwhile, teachers are also obliged to develop complete skills in the Merdeka curriculum, namely listening, speaking, reading, viewing, writing, and presenting.